Mysticism and Resistance: The Nature and Relevance of Ki Ageng Mangir’s Struggle Against the Mataram Sultanate - Wijaya, Wijaya; Rusli, Ris'an; Utami, Devi Aulia; Azwar, Alfi Julizun (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article critically examines the role of the legendary king Ki Ageng Mangir, who challenged the supremacy of the Sultanate of Mataram in sixteenth-century Java. Through a historical and semiotic approach, this study highlights how Ki Ageng Mangir combined Sufistic values, local traditions, as well as Islamic, Hindu, and Buddhist elements in his resistance against the expansionist Mataram sultanate. The Sufi path functioned as an instrument of legitimacy and effective symbolic resistance to the homogenization of ideology and political control. Values such as patience, sincerity, and God-reliance were the moral values that formed the character of Ki Ageng Mangir’s model of resistance, in contrast to the centralistic model of Panembahan Senopati and the integrative model of Sunan Kalijaga. This study found that local spirituality can serve as a means of individual enlightenment as well as the foundation for collective identity and communal resistance. Resistance to power hegemony can be manifested through meaningful religious and cultural expressions, affirming the relevance of traditional spirituality as the basis for legitimacy, identity, and resistance.